Exploring Carbon Sequestration Potential Across Various Clones in Teak Plantation - Subba, Susmita; Honnurappa, Shivanna (International Journal of Economic Plants, 2024)
A study conducted during August, 2019- February, 2020 forty year old clonal teak plantation in Manchikere, Karnataka, showed substantial carbon sequestration potential across eight distinct clones, emphasizing the promising role of genetic diversity in enhancing carbon capture. The clone studied were MyHaD1, MyHaD4, MyHaV1, MyHaV3, MyHaK2, MySA1, MyHuT1and MyMK3.The recognition and propagation of superior clones are crucial for enhancing carbon sequestration, aiding in the absorption and storage of atmospheric carbon dioxide.The diverse performance observed among the eight clones in the clonal teak plantation underscores the critical role of genetic diversity in shaping key parameters such as girth at breast height, volume, and biomass accumulation. Measurements of volume, aboveground biomass (AGB), belowground biomass (BGB), and soil carbon stock, along with nitrogen (N), phosphorus (P), and potassium (K) levels, were conducted. Carbon sequestration potential per tree varied, with all individuals contributing 395.56 t ha-1. MySA1 showed the highest potential (3.85 t), followed by MyHaD4 (3.08 t), and MyHaV1 recorded the least (1.46 t). Soil analysis revealed available N, P, and K concentrations, and the total carbon sequestration rate was 69.55 tha-1. The organic carbon (OC) content was 1.98% and 1.61%. This emphasizes the importance of factoring in both genetic diversity and soil nutrient dynamics to optimize carbon management in teak plantations effectively.